Molecular Characterization of Severe Acute Respiratory Syndrome Coronavirus 2 Isolates From Central Inner Sardinia - Malune, Paolo; Piras, Giovanna; Monne, Maria; Fiamma, Maura; Asproni, Rosanna; Fancello, Tatiana; Manai, Antonio; Carta, Franco; Pira, Giovanna; Fancello, Patrizia; Rosu, Valentina; Uras, Antonella; et al. (Frontiers in Microbiology, 2022)
Abstract Background: The SARS-CoV-2 pandemic stimulated an outstanding global sequencing effort, which allowed to monitor viral circulation and evolution. Nuoro province (Sardinia, Italy), characterized by a relatively isolated geographical location and a low population density, was severely hit and displayed a high incidence of infection. Methods: Amplicon approach Next Generation Sequencing and subsequent variant calling in 92 respiratory samples from SARS-CoV-2 infected patients involved in infection clusters from March 2020 to May 2021. Results: Phylogenetic analysis displayed a coherent distribution of sequences in terms of lineage and temporal evolution of pandemic. Circulating lineage/clade characterization highlighted a growing diversity over time, with an increasingly growing number of mutations and variability of spike and nucleocapsid proteins, while viral RdRp appeared to be more conserved. A total of 384 different mutations were detected, of which 196 were missense and 147 synonymous ones. Mapping mutations along the viral genome showed an irregular distribution in key genes. S gene was the most mutated gene with missense and synonymous variants frequencies of 58.8% and 23.5%, respectively. Mutation rates were similar for the S and N genes with one mutation every 788 nucleotides and every 712 nucleotides respectively. Nsp12 gene appeared to be more conserved, with one mutation every 1,270 nucleotides. The frequency of variant Y144F in the spike protein deviated from global values with higher prevalence of this mutation in the island. Conclusions: The analysis of the 92 viral genome highlighted evolution over time and identified which mutations are more widespread than others. The high number of sequences also permits the identification of subclusters that are characterized by subtle differences, not only in terms of lineage, which may be used to reconstruct transmission clusters. The disclosure of viral genetic diversity and timely identification of new variants is a useful tool to guide public health intervention measures.